FATP1 Exerts Variable Effects on Adipogenic Differentiation and Proliferation in Cells Derived From Muscle and Adipose Tissue - Huang, Jieping; Guo, Duo; Zhu, Ruirui; Feng, Ye; Li, Ruirui; Yang, Xintong; Shi, Deshun (Frontiers in Veterinary Science, 2022)
In livestock, intramuscular adipose tissue is highly valued whereas adipose tissue in other depots is considered as waste. Thus, genetic factors that favor fat deposition in intramuscular compartments over that in other adipose depots are highly desirable in meat-producing animals. Fatty acid transport 1 (FATP1) has been demonstrated to promote cellular fatty acid uptake and metabolism; however, whether it also influences cellular lipid accumulation remains unclear. In the present study, we investigated the effects of FATP1 on the differentiation and proliferation of adipocytes in five types of cells derived from muscle and adipose tissue and estimated the effects of FATP1 on intramuscular fat (IMF) deposition. We showed that FATP1 is mainly expressed in heart and muscle tissue in buffaloes as well as cells undergoing adipogenic differentiation. Importantly, we found that FATP1 promoted the adipogenic differentiation of muscle-derived cells (buffalo myocytes and intramuscular preadipocytes and mouse C2C12 cells) but did not affect, or even inhibited, that of adipose-derived cells (buffalo subcutaneous preadipocytes and mouse 3T3-L1 cells, respectively). Correspondingly, our results further indicated that FATP1 promotes IMF deposition in mice in vivo. Meanwhile, FATP1 was found to enhance the proliferative activity of all the assessed cells, except murine 3T3-L1 cells. These results provide new insights into the potential effects of FATP1 on IMF deposition, especially regarding its positive effects on meat quality in buffaloes and other livestock.